2020
DOI: 10.1538/expanim.19-0119
|View full text |Cite
|
Sign up to set email alerts
|

Female C57BL/6 and BALB/c mice differently use the acoustic features of male ultrasonic vocalizations for social preferences

Abstract: Male mice emit ultrasonic vocalizations (USVs) in response to the presence of female mice and their urine. Male USVs attract females, enhancing female reproductive functions, and are thus considered as the courtship song. Previous studies have shown that female mice exhibit disassortative social preferences for male USVs. However, it remains unclear what acoustic features female mice use for the development of these preferences. To address this, we examined social preferences of female C57BL/6 and BALB/c mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In four male mice groups, dominant calls from the chaser stimulated the speed of locomotion in the recipient males, indicating that the USV can convey emotional information from the emitter to modulate social behavior in the recipient (Sangiamo et al, 2020). We reported playback experiments in which male USVs were regenerated by the ultrasound emitter and observed the behavioral changes in females (Asaba et al, 2014;Nomoto et al, 2018Nomoto et al, , 2020. These reports revealed that females can recognize some specific characteristics of male USVs and show approaching behavior in response to the USVs.…”
Section: Discussionmentioning
confidence: 93%
“…In four male mice groups, dominant calls from the chaser stimulated the speed of locomotion in the recipient males, indicating that the USV can convey emotional information from the emitter to modulate social behavior in the recipient (Sangiamo et al, 2020). We reported playback experiments in which male USVs were regenerated by the ultrasound emitter and observed the behavioral changes in females (Asaba et al, 2014;Nomoto et al, 2018Nomoto et al, , 2020. These reports revealed that females can recognize some specific characteristics of male USVs and show approaching behavior in response to the USVs.…”
Section: Discussionmentioning
confidence: 93%
“…Such strain‐dependent patterns of call categories could affect mate‐choice and/or probability to interact with a conspecific. Additional studies are needed to better understand the role and characteristics of vocal communication during social interactions (e.g., differences between courtship and mating or USV production) across strains, since few studies have detailed this aspect so far 71,72 …”
Section: Discussionmentioning
confidence: 99%
“…Additional studies are needed to better understand the role and characteristics of vocal communication during social interactions (e.g., differences between courtship and mating or USV production) across strains, since few studies have detailed this aspect so far. 71,72 It is worth highlighting that USVs are a useful tool for evaluating emotion and motivation in rodents. 73,74 In juvenile and adult rats, call categories have been extensively used as measures of emotional/ affective state.…”
Section: Discussionmentioning
confidence: 99%
“…Besides approach behavior, female mice exhibit a preference toward a particular type of male USVs. Studies showed that female mice stayed longer near a sound source of one type of USVs than that of another type of USVs in experiments in which two USVs were played back simultaneously ( Musolf et al, 2010 ; Asaba et al, 2014 ; Nomoto et al, 2020 ). Specifically, our previous studies demonstrated that female mice preferred male USVs of a different strain than themselves ( Asaba et al, 2014 ; Nomoto et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that female mice stayed longer near a sound source of one type of USVs than that of another type of USVs in experiments in which two USVs were played back simultaneously ( Musolf et al, 2010 ; Asaba et al, 2014 ; Nomoto et al, 2020 ). Specifically, our previous studies demonstrated that female mice preferred male USVs of a different strain than themselves ( Asaba et al, 2014 ; Nomoto et al, 2020 ). These studies also revealed that pre-exposure of a male pheromone, exocrine gland-secreting peptide 1 (ESP1) ( Haga et al, 2010 ), was necessary for females’ USVs preferences.…”
Section: Introductionmentioning
confidence: 99%